Selected film essays and interviews / Bruce F. Kawin - Kawin, Bruce F.
This engaging collection of Bruce F. Kawin’s most important film essays (1977–2011) is accompanied by his interviews with Lillian Gish (1978) and Howard Hawks (1976). The Hawks interview is particularly concerned with his work with William Faulkner and their friendship. The Gish interview emphasizes her role as a producer in the 1920s. The essays focus on such topics as violence and sexual politics in film, the relations between horror and science fiction, the growth of video and digital cinema and their effects on both film and film scholarship, the politics of film theory, narration in film, and the relations between film and literature. Among the most significant articles reprinted here are “Me Tarzan, You Junk,” “The Montage Element in Faulkner's Fiction,” “The Mummy’s Pool,” “The Whole World Is Watching,” and “Late Show on the Telescreen: Film Studies and the Bottom Line.” The book includes close readings of films from “La Jetée” to “The Wizard of Oz.”